COMPETENCIES AND INNOVATIONS LABS: HUMANITIES IN ENGINEERS’ HIGH-EDUCATION - Stepien, T. (Journal of Human Capital Development (JHCD), 2012)
The contemporary system of science, research and high education need a new approach concerning engineers’ education because of the accelerated technological development. One of the main task remains the reinvention of education which shall make a new strategy for development (Arciszewski, 2009). At the beginning of the 21st century the new age of creativity and innovation is broken out (Prahalad, Krishnan 2010). And the new creative and innovative attitude concerns also the new destination of knowledge and education and the new definition of the essential outcomes of science, research and education in the future. One of the most important subject in this context is the necessity to elaborate a new orientation concerning the question of competencies’ formation adequately to the new forms and structures of the informational and knowledge-based society. In particular this applies to the key or core competencies as an expression of the ability to self-realization and selfimprovement, to the social integration and employment, but also to the attitude as an active citizen. In according to the recommendation of the European Parliament (2006) concerning the key and core competencies the process of lifelong learning bases on the development of the informational, technological and engineer’s, but also on the formation of the communicative, social and civil competencies as the components of the ability to implement the idea of lifelong learning. The other principal question concerns the importance of innovations. The knowledge-based society and economy suppose a permanent process of development and implementation of innovations, which are at the same time the decisive and determinant element of social, economic, technological and cultural development. This interdependence concerns the principal – connected and dependent to each other – areas of the modern society and culture: economy, medias and science from the one, and education, social supporting and social communication from the other hand. The degree or level of innovations but also the innovations deficit in these areas has directly a bearing on the condition and function of the whole system. These assumptions demarcate the stages in the following analysis but also the works in the two different basic-research projects elaborated at the Humanities’ Department the Wroclaw University of Technology in form of two humanistic laboratories on the point of junction between humanities, social science, culture studies, pedagogics and engineering science: “Competencies’ Lab” and “Innovations’ Lab”. The both – competencies and innovations – complement and condition each other with regard to the improvement of the creative potentiality in research and teaching/learning process, and with the high education herself as an interdisciplinary subject of research and studies (Kwiek 2010). KEYWORDS: key and core competencies; humanities and engineers high education; transdisciplinary / comparative education and research